Diabetes and Ramadan: Utility of flash-glucose monitoring derived markers of glycaemic control and comparison with glycosylated haemoglobin. (July 2019) - Saadane, Ilham; Ashraf, Tanveer; Ali, Tomader; Lessan, Nader
Abstract: Aims: Flash glucose monitoring (FGM)-derived markers of glucose control and variability and laboratory measured HbA1c among patients with diabetes on insulin in context of Ramadan fasting (RF) were examined and compared. Methods: FGM data on insulin-treated patients (n = 20, age 42.3 ± 11.4 years; 18 male, 2 female; 13 with type 1 and 7 with type 2 diabetes) who fasted during Ramadan were used to calculate Q-score as an indicator of glycaemia before, during and after RF. Post-hoc analysis in a group of patients (n = 12) who had HbA1c available and appropriate for these periods was performed. Other relevant data were extracted from patient records. Results: Mean glucose (9.6 ± 1.32 v 10.78 ± 1.64 mmol/l; P < 0.0001) and Q-score increased significantly with Ramadan fasting and reduced after Ramadan. Post-hoc subgroup analysis showed a significant rise in eA1c (7.2 ± 0.4%; 55.0 ± 4.4 mmol/mol v 7.7 ± 0.5%; 61.0 ± 5.5 mmol/mol) but not in laboratory HbA1c with Ramadan fasting; eA1c reduced after Ramadan (P = 0.018). Conclusions: Ramadan fasting was associated with a deterioration in overall glucose control and time in hyperglycaemia in insulin-treated patients. FGM-derived markers are useful and a preferable alternative to HbA1c in Ramadan studies.